Outcomes : NVQs and the emerging model of education and training - Jessup, Gilbert [Verfasser] (Falmer Press, 1991)
"Outcomes provides an account of the concepts and philosophy behind the creation of the National Vocational Qualification Framework and the model of education and training that it implies. It illustrates how some aspects of the model are being applied to general education and, if extended, could lead to the creation of an overall framework for education and training. The potential of the model is, however, not well understood: Outcomes attempts to remedy this. The book looks at the implication of the changing model of education and training for industry, further education, schools and colleges and for the learners themselves." (Publisher, BIBB-Doku)
Keywords: I 2.2.1 Westeuropa; Berufliche Qualifikation; Berufsbildung; Nationaler Qualifikationsrahmen; Kompetenzmodell; Lernmethode; Großbritannien